EVALUATING THE IMPACT OF DECRIMINALIZATION, RECLASSIFICATION, AND DEPENALISATION OF PETTY OFFENCES ON NIGERIA’S CRIMINAL JUSTICE ADMINISTRATION - Abhavan Ngwoke, Rita; Mbano, Ibiene Pamela (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
The overcriminalization of petty offences in Nigeria disproportionately affects individuals from poor or vulnerable backgrounds, exacerbating socio-economic inequalities and overburdening the criminal justice system. This issue of global concern contradicts critical human rights agreements such as the International Covenant on Social, Economic and Cultural Rights, the principles of decriminalization of petty offences adopted by the African Commission in 2017 and the Ouagadougou Declaration and Plan of Action on Accelerating Prisons and Penal Reforms in Africa. These petty offences, often remnants of colonial laws, undermine the dignity of African people by criminalizing behaviours linked to economic hardship such as street vending, loitering, begging, sex work, nuisance, breach of peace, etc. This study aims to examine the impact of decriminalizing, reclassifying, and depenalizing petty offences in Nigeria’s criminal justice system, highlighting how these legal reforms can address socio-economic issues without stigmatizing poverty. Utilizing a doctrinal research methodology that incorporates historical and comparative sources, and supported by case studies, this research exposes the exploitative role of law enforcement agents and how this obstruct and over-burden the current system. Findings also reveal how vague and overly broad terms of petty offences lead to indiscriminate arrests, exploitation, and manipulation of charges. The paper recommends that a more efficient criminal justice system would be realized through penal reform, either by decriminalization, depenalization or reclassification, depending on the nature of the offence. Such reforms are projected to reduce the criminal justice system’s burden, decrease the criminalization of poverty and promote more equitable outcomes for vulnerable individuals in Nigeria